Science periodicals in the nineteenth and twenty-first centuries - Shuttleworth, S; Charnley, B (Royal Society, 2016)
From around 100 titles worldwide at the beginning of the nineteenth century, the number of science periodicals grew to an estimated 10 000 by the end, facilitating in the process an exponential growth in popular and professional forms of science. Nowadays, scientists might take it for granted that publication in a scientific journal is the recognized way to communicate results, but it was only in the early nineteenth century that this practice started to become routine: communication by personal letter or lecture had previously been equally acceptable modes. Although there has been excellent scholarship on individual aspects of the rise of the scientific journal, more detailed work is needed to understand where the scientific periodical in all its various forms came from, where it might be going and how it has operated over time and in relation to the scientific enterprise. In this issue we bring together a series of papers on the rise of the science journal, while also placing such developments in the context of the challenges facing contemporary science publishing at a moment when it looks like the twenty-first century science journal, in its physical printed form, might cease to exist.